Antibacterial Properties of Bacterial Endophytes Isolated from the Medicinal Plant Origanum heracleoticum L. - Giulia Semenzato; Alberto Bernacchi; Sara Amata; Angela Bechini; Fabiola Berti; Carmela Calonico; Valentina Catania; Antonia Esposito; Anna Maria Puglia; Antonio Palumbo Piccionello; Giovanni Emiliani; Sauro Biffi; et al. (Frontiers in Bioscience-Landmark, 2024)
Background: Bacterial endophytic communities associated with medicinal plants synthesize a plethora of bioactive compounds with biological activities. Their easy isolation and growth procedures make bacterial endophytes an untapped source of novel drugs, which might help to face the problem of antimicrobial resistance. This study investigates the antagonistic potential of endophytic bacteria isolated from different compartments of the medicinal plant O. heracleoticum against human opportunistic pathogens. Methods: A panel of endophytes was employed in cross-streaking tests against multidrug-resistant human pathogens, followed by high-resolution chemical profiling using headspace-gas chromatography/mass spectrometry. Results: Endophytic bacteria exhibited the ability to antagonize the growth of opportunistic pathogens belonging to the Burkholderia cepacia complex (Bcc). The different inhibition patterns observed were related to their taxonomic attribution at the genus level; most active strains belong to the Gram-positive genera Bacillus, Arthrobacter, and Pseudarthrobacter. Bcc strains of clinical origin were more sensitive than environmental strains. Cross-streaking tests against other 36 human multidrug-resistant pathogens revealed the highest antimicrobial activity towards the Coagulase-negative staphylococci and Klebsiella pneumoniae strains. Interestingly, strains of human origin were the most inhibited, in both groups. Concerning the production of volatile organic compounds (VOCs), the strain Arthrobacter sp. OHL24 was the best producer of such compounds, while two Priestia strains were good ketones producers and so could be considered for further biotechnological applications. Conclusions: Overall, this study highlights the diverse antagonistic activities of O. heracleoticum-associated endophytes against both Bcc and multidrug-resistant (MDR) human pathogens. These findings hold important implications for investigating bacterial endophytes of medicinal plants as new sources of antimicrobial compounds.